PENGARUH RELASI GENDER DAN PENGAMBILAN KEPUTUSAN TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI (SMP NEGERI) DI KECAMATAN BEKASI SELATAN KOTA BEKASI - RATU DIAN HATIFAH (Jurnal Manajemen Pendidikan, 2015)
The objective of this research is to know the effect of gender relation and decision making toward job performance of the teachers at State Junior High School at south Bekasi district, Bekasi City. The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 201 teachers. Research samples selected as much as 134 teachers using simple random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) the gender relation have positive direct effect to job performance; (2) the decision making have positive direct effect to job performance; (3) the gender relation have positive direct effect to decision making. The performance can be improved through improvement of gender relation and the decision making.